2001
DOI: 10.1088/0305-4470/34/47/324
|View full text |Cite
|
Sign up to set email alerts
|

Geometry of entangled states, Bloch spheres and Hopf fibrations

Abstract: We discuss a generalization of the standard Bloch sphere representation for a single qubit to two qubits, in the framework of Hopf fibrations of highdimensional spheres by lower dimensional spheres. The single-qubit Hilbert space is the three-dimensional sphere S 3 . The S 2 base space of a suitably oriented S 3 Hopf fibration is nothing but the Bloch sphere, while the circular fibres represent the overall qubit phase degree of freedom. For the two-qubits case, the Hilbert space is a seven-dimensional sphere S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
295
0
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 168 publications
(301 citation statements)
references
References 5 publications
(12 reference statements)
2
295
0
4
Order By: Relevance
“…For pure states, the concurrence, which is an established measure of entanglement, is C = 2|α 1 α 4 −α 2 α 3 | [20]. (The separability criterion α 1 α 4 − α 2 α 3 = 0 has also been derived from a Hilbert space geometrical viewpoint in [33].) Our measure Γ, on the other hand, is Γ = 2||α 1 α * 4 | − |α 2 α * 3 || ≤ C. Equality is only achieved if either the complex vectors α 1 α 4 and α 2 α 3 are parallel, or if at least one of the coefficients α 1 , .…”
Section: An Experimental Implementationmentioning
confidence: 99%
“…For pure states, the concurrence, which is an established measure of entanglement, is C = 2|α 1 α 4 −α 2 α 3 | [20]. (The separability criterion α 1 α 4 − α 2 α 3 = 0 has also been derived from a Hilbert space geometrical viewpoint in [33].) Our measure Γ, on the other hand, is Γ = 2||α 1 α * 4 | − |α 2 α * 3 || ≤ C. Equality is only achieved if either the complex vectors α 1 α 4 and α 2 α 3 are parallel, or if at least one of the coefficients α 1 , .…”
Section: An Experimental Implementationmentioning
confidence: 99%
“…The role of entanglement in the phase evolution of two-qubit systems was investigated in refs. [13,14], and the topological nature of the corresponding geometric phases was investigated both theoretical [15][16][17] and experimentally in the context of spin-orbit transformations on a paraxial laser beam [18] and in nuclear magnetic resonance [19]. In a recent work, we investigated the crucial role played by the dimension of the Hilbert space on the topological phases acquired by entangled qudits [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…It can be shown that in that case, the π phase also occur. However, the relation between non MES and the SO(3) group is more complex [6], as well as the geometrical interpretation of their time evolution. …”
mentioning
confidence: 99%